Planning of Optimal Raw Materials Inventory Using the Marcov Chain Method - Rina Handayani; Manaek Hamonangan Sihombing (PT Inovasi Pratama Internasional, 2022)
Inventory is an important issue to control. Both finished goods and raw material inventories are the same with ingredient raw for the production process . no seldom our find problem where company no To do good control _ in management inventory that results in needs customer no fulfilled . Ray Traso Jaya is company that manufactures and sells paving block products , bataco , riol concrete and pits wind where in the production process experience disturbance in carry out the production process caused level management supply ingredient raw sand and cement that are not optimal as a result company difficulty for Fulfill needs customers who are fluctuating . Formulas problem in study this is